2009
DOI: 10.2967/jnumed.108.059733
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of Tumor Blockage and Rerouting of Lymphatic Drainage in Penile Cancer Patients by Use of SPECT/CT

Abstract: The reliability of sentinel node biopsy is dependent on the accurate visualization and identification of the sentinel node(s). It has been suggested that extensive metastatic involvement of a sentinel node can lead to blocked inflow and rerouting of lymph fluid to a ''neo-sentinel node'' that may not yet contain tumor cells, causing a false-negative result. However, there is little evidence to support this hypothesis. Recently introduced hybrid SPECT/ CT scanners provide both tomographic lymphoscintigraphy and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 111 publications
(45 citation statements)
references
References 29 publications
3
39
1
2
Order By: Relevance
“…80). These experimental findings are in agreement with the clinically observed redirection of lymph flow after LN metastasis of penile cancers (82). Bypassing of metastatic LNs with increased intranodal pressure toward the next echelon of nodes with lower intranodal pressure has also been reported in breast cancer (83).…”
Section: Functional Quantitative In Vivo Imaging Of Tumor-draining Lsupporting
confidence: 89%
“…80). These experimental findings are in agreement with the clinically observed redirection of lymph flow after LN metastasis of penile cancers (82). Bypassing of metastatic LNs with increased intranodal pressure toward the next echelon of nodes with lower intranodal pressure has also been reported in breast cancer (83).…”
Section: Functional Quantitative In Vivo Imaging Of Tumor-draining Lsupporting
confidence: 89%
“…Indeed, Kwon et al [26] have reported that lymphatic drainage can occur across the midline of the animal in response to cancer metastasis. In humans, SPECT/CT imaging has shown lymphatic re-routing in response to cancer metastasis [27]. Recently it has been reported that functional intraluminal valves prevent fluid communication between the lymphatic vessels and draining LN [28].…”
Section: Discussionmentioning
confidence: 99%
“…The main reason for false negative results is complete sentinel node replacement with tumor cells and identification of non-involved lymph nodes as sentinel nodes. 118 Our systematic review showed that sentinel node mapping is highly successful and accurate in small and low stage cervical cancer tumors. Due to its low accuracy, sentinel node mapping is not well suited for large tumors (>2 cm) and those at a more advanced stage.…”
Section: Tumor Size and Stagementioning
confidence: 98%